PENINGKATAN KETAHANAN PSIKOLOGIS KELUARGA MELALUI PELATIHAN KESADARAN EFIKASI DIRI DALAM PENDAMPINGAN ANAK BELAJAR DARI RUMAH SAAT PANDEMI COVID-19 BAGI ORANGTUA/WALI TK ABA NGANGGRING TURI SLEMAN DI YOGYAKARTA - Yuzarion, Yuzarion; Hidayah, Nurul; Yuniarti, Dini; Fakhruddiana, Fuadah; Selasih, Selasih; Casminto, Casminto (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2021)
The article on Community Service Program (PPM) is motivated by psychological problems, related to self-efficacy problems, the lack of skill of parents in assisting children to learn from home.The aim of the Community Service Program (PPM) is to increase the family psychological resilience. The PPM using training method was conducted at TK ABA Nganggring, Turi, Sleman, DI Yogyakarta. The training participants were 31 parents/ guardians of TK ABA Nganggring students. The training results showed an increasing in family psychological resilience through self-efficacy awareness training in accompanying for children home learning during the Covid-19 pandemic, with satisfactory results. The results of the self-efficacy awareness training are as follows; (1) participants have obtained new knowledge about awareness of self-efficacy, (2) participants have more confident in accompanying children's learning, (3) participants have more confident that children have enjoyed in learning, (4) participants have more confident, have readiness to assist children in learning, and ( 5) participants have more confident in ability to regulate emotion tension in assisting children's home learning during the Covid-19 pandemic. The PPM follow-up requires implementing sustainable programs, as well as mentoring parents/ guardians of TK ABA Nganggring Turi Sleman Yogyakarta. So that PPM family psychological resilience to parents/guardians of TK ABA Nganggring Turi Sleman, continue to be sustainable and can be maximized so that children will feel enjoyment and comfortable at home learning as long as the occurrence of covid-19 pandemic.